Maternal Reflective Method in the Use of Short Story of Daily Living Card to Practice Speech Skills on Students with Hearing Impairments - Murdiyani, Kenanga Kusuma; Hermanto, Hermanto; Pamungkas, Bayu (Department of Special Education, 2022)
The Indonesian government issued the regulation on Distance Learning during the pandemic as stated in the Higher Education Law Number 12 of 2021 Article 31 concerning Distance Learning. This learning style is quite problematic, especially when applied to students with special needs. One type of student with special needs who have difficulty carrying out the online learning process is students with hearing impairments. As a result, some adjustments are required to accommodate those students during the distance learning process. One of those adjustments includes modifying the learning method, which is implemented with the maternal reflective method using the Short Story of Daily Living Card. This study aims at developing the Short Story of Daily Living Card as a medium to implement the Maternal Reflective Method (MRM) for students with hearing impairments during the pandemic. This study uses the Research and Development (R&D) method, which includes the stages of analysis, design, development, implementation, and evaluation. The study is only limited to the design step. The results shows that educators had difficulties in providing speech learning for students with hearing impairment. As a result, Short Story of Daily Living Card can help teachers and parents in providing speech practice for students.